(untitled) (Development Service Industry Management, 2024)
The article examines the main methods of analyzing the potential of tourism enterprises in communities and various approaches to evaluating their capacity to determine the tourism attractiveness of these areas and to develop prospective development strategies, taking into account the existing tourism infrastructure. The relevance of the study lies in the systematization of modernized approaches to assessing the potential of service sector firms that found themselves in crisis conditions following a series of economic shocks caused by the pandemic and the suspension of tourism activities at the onset of the full-scale invasion. The article presents methodologies for evaluating the economic, financial, competitive, and investment potentials of tourism enterprises, with proposed modifications tailored to new realities. Key indicators of sustainable entrepreneurship development in the tourism sector have been analyzed, in alignment with Ukraine’s Sustainable Development Goals for 2030. General scientific methods of inquiry, such as induction and deduction, association and analogy, analysis, and synthesis, were employed in the research. The study revealed that, given economic instability and the anticipated transition of the global economy to Industry 5.0, it is necessary to apply modernized methods for assessing various types of potential in tourism enterprises, adapted to emerging challenges. In the context of martial law and post-crisis economic recovery, Ukraine’s domestic tourism requires comprehensive reform, including the diversification of the tourism market, the development of investment policies, and the retention of a focus on the local market during the post-war period, alongside efforts to attract international tourists. The practical significance of the research lies in the potential application of the proposed methodologies by tourism businesses and the use of assessment results by communities to formulate sustainable development strategies. These strategies would align with the structure of the modern tourism market, meet the needs of consumers, and address the priorities of local residents. Importantly, the management system of tourism enterprises will be effective only if the goals of each subsystem are aligned with the priority objectives of territorial community development.